Integrasi Psikologi dan Tasawuf dalam Menangani Dampak Toxic Masculinity pada Kesehatan Mental Pria - Abadi, Muhammad Zidan (Psikodidaktika, 2024)
Toxic masculinity refers to social norms that encourage men to fulfil rigid standards of masculinity, such as obstinacy, emotional avoidance, and dominance, which often have a negative impact on mental health, including anxiety, depression, and difficulty building healthy social relationships. This study aims to explore the integration between psychology and Sufism as a more holistic approach in addressing the impact of toxic masculinity. The method used was qualitative analysis with a literature review, which included an understanding of toxic masculinity, psychological techniques such as Cognitive Behavioural Therapy (CBT) and Emotion Regulation Theory (ERT), and Sufism principles such as muhasabah, dhikr, and tazkiyah al-nafs. The results showed that while modern psychological approaches are effective in managing emotions and maladaptive thought patterns, integration with Sufism provides a deeper spiritual dimension in mental health recovery. With this integrative approach, men affected by toxic masculinity can manage their emotions and behaviours more effectively and achieve a balance between psychological and spiritual aspects. This study concludes that the integration of psychology and Sufism can be a more comprehensive and sustainable solution in addressing the problem of toxic masculinity in men.